A Study on the effectiveness of child care policy in Korea - Lee, Haywon (The Korea Institute of Public Finance SeoulKR, 2013)
Analyses whether the current child care policy has been designed in such a way as to achieve the effects expected from the financial support, and then suggests future policy guidelines.